On real bounded and regular (n − k, k)–line KP solitons - Simonetta Abenda (Bruno Pini Mathematical Analysis Seminar, 2017)
After reviewing some of the recent results by S. Chakravarty and Y. Kodama and by Y. Kodama and L. Williams concerning the characterization of the asymptotic behavior of real regular and bounded multi–line soliton solutions to the KP-II equation, we introduce the finite–gap approach to the inverse spectral problem for this family of solutions.